Focal liver lesions: interobserver and intraobserver agreement of three-dimensional contrast-enhanced ultrasound-assisted volume measurements - Tommaso Vincenzo Bartolotta; Antonio Sidoti Pinto; Roberto Cannella; Giorgia Porrello; Rossana Taravella; Angelo Randazzo; Adele Taibbi (Ultrasonography, 2021)
Purpose This study was conducted to assess the interobserver and intraobserver agreement of three-dimensional contrast-enhanced ultrasound (3D-CEUS) volume calculations of focal liver lesions (FLLs). Methods Thirty-nine patients (15 men and 24 women; mean age, 55.4 years) with 39 FLLs (mean size, 3.1±1.8 cm; size range, 1 to 8 cm) prospectively underwent 3D-CEUS. Four readers calculated the volume of each lesion in an independent and blinded fashion in two separate sessions by means of a semi-automatic, commercially available proprietary software. The differences in lesion volumes (cm3) among sessions and readers were assessed using the Mann-Whitney U test and the Kruskal-Wallis test. Bland-Altman analysis was also performed. Intraclass correlation coefficients (ICCs) with 95% confidence intervals (95% CIs) were calculated. The statistical significance level was set at P<0.05. Results Among readers, there were no statistically significant differences in the first (P=0.953) and second (P=0.592) reading sessions for volume calculations of the 39 FLLs, with almost perfect inter-reader agreement (ICC values of the first reading session, 0.996; 95% CI, 0.992 to 0.998 and ICC value of the second reading session, 0.994; 95% CI, 0.990 to 0.997, respectively). For each of the four readers, there were no significant differences in volume calculations between the two sessions (P=0.503-0.924), and the intrareader agreement was almost perfect for each reader (R1: ICC, 0.995; 95% CI, 0.991 to 0.998; R2: ICC, 0.995; 95% CI, 0.988 to 0.997; R3: ICC, 0.996; 95% CI, 0.992 to 0.998; R4: ICC, 0.985; 95% CI, 0.971 to 0.992). Conclusion 3D-CEUS volume calculations provided consistent measurements across different readers with almost perfect intrareader agreement.